Urban-Biased Structural Change - Natalie Chen; Dennis Novy; Carlo Perroni; Horng Chern Wong (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using firm-level data from France, we document that the shift of economic activity from manufacturing to services over the last few decades has been urban-biased: structural change has been more pronounced in areas with higher population density. This bias can be accounted for by the location choices of large services firms that sort into big cities and large manufacturing firms that increasingly locate in suburban and rural areas. Motivated by these findings, we estimate a structural model of city formation with heterogeneous firms and international trade. We find that agglomeration economies have strengthened for services but weakened for manufacturing. This divergence is a key driver of the urban bias but it dampens aggregate structural change. Rising manufacturing productivity and falling international trade costs further contribute to the growth of large services firms in the densest urban areas, boosting services productivity and services exports, but also land prices.
Keywords: F15; F61; R12; R14; 330; agglomeration; cities; export; firm sorting; manufacturing; productivity; services; trade costs